Both muscle mass and muscle strength are inversely associated with depressive symptoms in an elderly Chinese population. (7th June 2016) - Wu, Hongmei; Yu, Bin; Meng, Ge; Liu, Fangfang; Guo, Qi; Wang, Jiazhong; Du, Huanmin; Zhang, Wen; Shen, Suxing; Han, Peipei; Dong, Renwei; Wang, Xiuyang; et al.
Abstract : Objective: Few population studies have examined the association between skeletal muscle and depressive symptoms. The aim of this study was to examine whether low muscle mass and muscle strength were associated with the depressive symptoms in elderly Chinese. Methods: A cross‐sectional study was conducted with 1046 elderly in Tianjin, China. Depressive symptoms were examined using the 30‐item Geriatric Depression Scale. A Geriatric Depression Scale score of ≥11 was used to indicate depressive symptoms. Skeletal muscle mass was indicated using a skeletal muscle mass index (SMI) that was measured by bioimpedance analysis and muscle strength was measured by dynamometer. Results: In a multiple logistic regression analysis, subjects in the lowest quartile of SMI or muscle strength had a significantly higher risk for depressive symptoms compared with those in the fourth quartile. The odds ratios and 95% confidence interval for depressive symptoms risk in the lowest quartile of SMI compared with the highest after adjusting for potential confounding factors were 10.1 (2.25, 58.3) in men and 3.17 (1.07, 9.95) in women. The odds ratios (95% confidence interval) for depressive symptoms risk in the lowest quartile of muscle strength compared with the highest after adjusting for potential confounding factors were 2.55 (1.02, 6.67) in men and 4.18 (1.83, 10.2) in women. Conclusions: Both muscle mass and muscle strength are inversely associated with depressive symptoms in elderly Chinese. These findings may provide novel insights linking skeletal muscle and depressive symptoms. Copyright © 2016 John Wiley & Sons, Ltd.